Familial Identity Theft - Navarro, John (American journal of criminal justice, 2017)
Reports of identity theft in the U.S. have risen since the 2000s, which has resulted in financial losses into the billions. Along with this rise is the increased likelihood of familial identity theft. In this study, the differences between familial and non-familial identity theft were explored through the January–July 2012 Identity Theft Supplement collected with the National Crime Victimization Survey. Results showed that family member victims were likely to have experienced one type of identity theft more often than non-family victims were, personal information used for other fraudulent purposes, which included government benefits and driver’s licenses. Factors that allowed for a respondent’s personal information used for other fraudulent purposes included family membership, young persons in the household, and repeat victimization. Findings suggest that few factors can predict the likelihood to experience the misuse of personal information and that familial identity theft may be difficult to detect.